Transformation of Educational Work in State-established Galleries in the Czech Republic – situation in Moravian Gallery - Rozbořil, Blahoslav; Kaňkovská, Andrea (Tudásmenedzsment, 2023)
The paper deals with the transformation of educational activities in relation to other activities and strategies towards the public in state-established galleries in the Czech Republic. The case study of the Moravian Gallery in Brno highlights the opening up of the gallery to the public and the introduction of new formats for working with the public. It is a mono-layered process that may not be perceived very positively by the art theoretical community. The professional community perceives new promotion formats such as the extension of animation activities to elements of gamification in the case of institutions with long traditions and ties to high culture, as an invasion of low-culture elements. Economic considerations are also a target of criticism: the criterion for the success of a gallery for the founder is the growth or retention of visitors. However, the innovation of educational programmes and the audience development plan do not generate growth in attendance, but above all bring the a transformation of the spectrum and the structure of the visitor base. The solution to the dilemma of elitist versus egalitarian orientation seems obvious: if a museum institution is to be visible and attractive, it must necessarily be in the egalitarian pole in the competition between attractive media and social networks, otherwise it will become an exclusively academic institution. It is questionable to what extent the new strategies for working with audiences are functional in the Czech environment as a manifestation of the democratisation of art in cultural institutions.